Off Pump CABG along with Resection of Giant Thymoma : A Case Report - Kamruzzaman, M; Rahman, KMA; Hosain, N; Ahsan, N; Anam, S; Rahman, MMM (Cardiovascular Journal, 2014)
Coronary artery disease is the most common form of heart disease and the single most important cause of premature death world-wide. Thymomas are anterior mediastinal neoplasms, characterized by epithelial cells and lymphocytes. Although they are often encapsulated and well differentiated tumors, they can show local invasion, pleural invasion or extrathoracic metastasis. In this article, we report the case of a rare patient who underwent thymectomy along with off-pump coronary artery bypass graft surgery. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20801 Cardiovasc. j. 2014; 7(1): 55-57